Community acquired pneumonia—a prospective UK study. Issue 5 (1st November 2000) - Drummond, P; Clark, J; Wheeler, J; Galloway, A; Freeman, R; Cant, A
Abstract : BACKGROUND: There are few data on paediatric community acquired pneumonia (PCAP) in the UK. AIMS: To investigate the aetiology and most useful diagnostic tests for PCAP in the north east of England. METHODS: A prospective study of hospital admissions with a diagnosis of PCAP. RESULTS: A pathogen was isolated from 60% (81/136) of cases, and considered a definite or probable cause of their pneumonia in 51% (70/136). Fifty (37%) had a virus implicated (65% respiratory syncytial virus) and 19 (14%) a bacterium (7% group A streptococcus, 4% Streptococcus pneumoniae ), with one mixed infection. Of a subgroup (51 patients) in whom serum antipneumolysin antibody testing was performed, 6% had evidence of pneumococcal infection, and all were under 2 years old. The best diagnostic yield was from paired serology (34%, 31/87), followed by viral immunofluorescence (33%, 32/98). CONCLUSION: Viral infection accounted for 71% of the cases diagnosed. Group A streptococcus was the most common bacterial infective agent, with a low incidence of both Mycoplasma pneumoniae and S pneumoniae . Pneumococcal pneumonia was the most common bacterial cause of pneumonia in children under 2 years but not in older children. Inflammatory markers and chest x ray features did not differentiate viral from bacterial pneumonia; serology and viral immunofluorescence were the most useful diagnostic tests.